2018
DOI: 10.1128/jcm.00116-18
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Highly Sensitive Mycobacterium tuberculosis Complex Real-Time PCR Assay for Diagnosis of Pulmonary Tuberculosis in a Low-Prevalence Setting: a Prospective Intervention Study

Abstract: The potential impact of routine real-time PCR testing of respiratory specimens from patients with presumptive tuberculosis in terms of diagnostic accuracy and time to tuberculosis treatment inception in low-prevalence settings remains largely unexplored. We conducted a prospective intervention cohort study. Respiratory specimens from 1,020 patients were examined by acid-fast bacillus smear microscopy, tested by a real-time complex PCR assay (Abbott RealTi MTB PCR), and cultured in mycobacterial media. Seventee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Ten studies with 4858 respiratory specimens were included in the meta-analysis that evaluated Abbott RealTime MTB assay for TB detection [10][11][12][13][14][15][16][17][18][19] (figure 2). In all studies, the assay was run directly on specimens, as opposed to positive culture isolates.…”
Section: Abbott Realtime Mtbmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies with 4858 respiratory specimens were included in the meta-analysis that evaluated Abbott RealTime MTB assay for TB detection [10][11][12][13][14][15][16][17][18][19] (figure 2). In all studies, the assay was run directly on specimens, as opposed to positive culture isolates.…”
Section: Abbott Realtime Mtbmentioning
confidence: 99%
“…Pooled sensitivity was 88.4% (95% CI 74.0-99. WANG [19] VINUESA [17] VINUESA [18] TANG [16] TAM [15] SCOTT [14] HOFMANN-THIEL [13] HINIC [12] CHEN [11] BERHANU [ WANG [19] VINUESA [17] VINUESA [18] TANG [16] TAM [15] SCOTT [14] HOFMANN-THIEL [13] HINIC [12] CHEN [11] BERHANU [ demonstrated very low sensitivity of 41.0% (95% CI 18.0-67.0), which may partially be explained by the high prevalence of HIV in their study population, meaning that a high proportion of cases suffered from paucibacillary disease. We were not able to explore test performance by HIV status further as most of the studies (60%) did not report HIV prevalence.…”
Section: Sub-group Analyses: Smear Statusmentioning
confidence: 99%
“…The IS6110 sequence, which belongs to a family of ISs of the IS3 category with high specificity, has been widely applied for MTBC-PCR assays [24]. However, some M. tuberculosis strains lacking the IS6110 gene were found in several clinical investigations [25,26]. Thus, the mpb64 gene, which encodes the RD2 region of the MPB64 protein in the genome of M. tuberculosis [27], was introduced in our study, and it showed excellent specificity for MTBC strains in previous studies [9,27].…”
Section: Discussionmentioning
confidence: 99%
“…The IS6110 gene has been widely applied for PCR detections in the M. tuberculosis complex genome, which belongs to a family of IS of the IS3 category with high speci city [22]. However, some of M. tuberculosis strains absence of IS6110 gene were found in several clinical investigations during recent decades [23,24]. Therefore, in this research, we added another target gene, the mpb64 gene.…”
Section: Discussionmentioning
confidence: 99%